The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1155/2010/709371
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Hidradenoma Papilliferum

Abstract: Hidradenoma papilliferum is a rare tumor that occurs almost exclusively in females on the anogenital area. Rare cases of ectopic (nongenital) hidradenoma papilliferum have been described. The lesions usually present as an asymptomatic slow-growing, red, firm, mobile, well-delimitated nodule that grows for a long time before resection. We describe a case of an 26-year-old man that presented with an enlarging nodule on his right eyelid. The histological findings revealed a hidradenoma papilliferum. So far, among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
0
18
2
Order By: Relevance
“…A further three cases excluded from our review referred to two female patients with nipple lesions, because their tumors may actually have been papillary adenomas of the nipple rather than hidradenoma papilliferum, 2 and one male patient with a neoplasm on the right eyelid, in whom histopathological findings appeared to be more consistent with a diagnosis of syringocystadenoma papilliferum because an epidermal connection was evident 9 …”
Section: Summary Of Cases Of Ectopic Hidradenoma Papilliferum Reportementioning
confidence: 99%
“…A further three cases excluded from our review referred to two female patients with nipple lesions, because their tumors may actually have been papillary adenomas of the nipple rather than hidradenoma papilliferum, 2 and one male patient with a neoplasm on the right eyelid, in whom histopathological findings appeared to be more consistent with a diagnosis of syringocystadenoma papilliferum because an epidermal connection was evident 9 …”
Section: Summary Of Cases Of Ectopic Hidradenoma Papilliferum Reportementioning
confidence: 99%
“…1,3,10 The treatment of choice in our study was local excision which conforms to the most literature. 1,415 Although a few studies have reported recurrence following incomplete excision of the primary tumour.…”
Section: Discussionmentioning
confidence: 54%
“…This may explain the more frequent occurrence of ectopic HP in head and neck region. 2 Among the head and neck cases only 3 have been reported in the upper eyelid with the present case being the fourth one and first to occur in the lower eyelid [3][4][5] (Table). The clinical presentation and prognosis of ectopic tumors is similar to anogenital HP.…”
Section: Discussionmentioning
confidence: 67%
“…2,6 In conclusion, ectopic HP is a rare benign adnexal tumor and the present case is the first one to be reported in the lower eyelid. [3][4][5] As it can mimic various cutaneous lesions and their malignant counterparts, histopathological examination is required for correct diagnosis. Previously reported cases of ectopic hidradenoma papilliferum of eyelid …”
Section: Discussionmentioning
confidence: 99%